Comparison between the steady performance of double-entry and twin-entry turbocharger turbines - Romagnoli, Alessandro (2012)
Most boosting systems in internal combustion engines utilize “pulse turbocharging” to maximize the energy extraction by the turbine. An internal combustion engine with more than four cylinders has a significant overlap between the exhaust pulses which, unless isolated, can decrease the overall pulse energy and increase the engine pumping loss. Thus, it is advantageous to isolate a set of cylinders and introduce the exhaust gases into two or more turbine entries separately. There are two main types of multiple entry turbines depending on the method of flow division: the twin-entry and the double-entry turbine. In the twin-entry design, each inlet feeds the entire circumference of the rotor leading edge regardless of inlet conditions. In contrast, the double-entry design introduces the flow from each gas inlet into the rotor leading edge through two distinct sectors of the nozzle. This paper compares the performance of a twin and double-entry mixed flow turbine. The turbines were tested at Imperial College for a range of steady-state flow conditions under equal and unequal admission conditions. The performance of the turbines was then evaluated and compared to one another. Based on experimental data, a method to calculate the mass flow under unequal admission from the full admission maps was also developed and validated against the test results.